The sum could be greater than 1 but not equal to 1.
Answer:
If M is the midpoint, then LM = MN
3x - 2= 2x +1
x = 3
So LM = 3x - 2 = 9 -2 = 7
LM = 7
Answer:
61
Step-by-step explanation:
1. let the unknown be x
2. using theorem of Pythagoras that states the hypotenuse will be equal to the sum of the other two sides we can determine that 75=14+X
3. this implies that X=75-14
4. therefore X= 61
-5+6 = 1. This is the answer. Thank you
Answer:
It is an identity, the proof is in the explanation
Step-by-step explanation:
csc(A)-cot(A)=tan(A/2)
I'm going to start with right hand side
tan(A/2)=(1-cos(a))/(sin(a)) half angle identity
tan(A/2)=1/sin(a)-cos(a)/sin(a) separate fraction
tan(A/2)=csc(a)-cot(a) reciprocal and quotient identities